“Tratamiento fisioterapèutico preventivo de la huella plantar en niños a partir de 2 años de edad que asisten al centro infantil del buen vivir “francisco chiriboga” febrero- julio 2016” - Motoche Santos, Valeria Maribel (2017)
The research project is about the incidence of flat feet in the alterations of the plantar footprint, in the human body the feet is the base of support of all its weight and bone structure is fundamental if they acquire some pathology are going to affect On different important joints, in this case the event of the flat foot has been studied to be able to provide preventive physiotherapeutic treatment of the plantar footprint, the same that was applied in the Children's Center of the Buen Vivir Francisco Chiriboga in the city of Riobamba, to children and Girls from 2 years of age. Data were obtained in a population of 30 boys and girls, the following results were obtained: In the initial evaluation of plantar footprint, it was determined that of the total of the patients that were evaluated, 7% had a normal plantar footprint, 93% presented alterations in their plantar footprint, according to their age and development, respectively. In the initial assessment of the Hernández Corvo test to verify the area of the plantar arch by taking the plantar footprint, 65% of the population had flat feet, 28% flat / normal feet, and 7% were patients considered as feet Normal. In the final evaluation of the patient's footprints, the patient had normal traces 33% and 67% still had alterations. In the Hernández Corvo test in its final evaluation, we considered 30% of flat feet within the assessment, 33% normal flat feet and 37% of the population had normal feet. Finally, with these results, a guide of physiotherapeutic exercises for the plantar footprint (Risser), with information directed to parents and family mothers, is proposed to correct the flat foot in children of the Children's Center of the Buen Vivir Francisco Chiriboga. The application of physiotherapeutic exercises are used to improve the plantar vault, in order to achieve muscle strengthening of the foot, which will contribute to the strengthening of the plantar arch.